THE DEVELOPMENT OF MATHEMATICS LEARNING MODULE ON THE SUBJECT OF THE PATTERN OF SEQUENCE NUMBER AND SERIES ON CLASS X STUDENTS OF SMK - Yolanita Safitri; Uus Kusdinar (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2018)
This research is motivated by the absence of a mathematical learning module on the material of sequence numbers and series in school. This study aims to develop the module of mathematical learning on the material of the pattern of sequence number and series for class X students of Vocational High School (SMK), which is used as independent teaching materials of the students. This research using the Research and Development (R&D) method with the ADDIE model consisting of five main stages: analysis, design, development, implementation, and evaluation. This study's subjects are material experts, media experts, and vocational school students in two schools: SMKN 1 Pleret and SMK Diponegoro Depok. The data collection method techniques using questionnaires. Simultaneously, the data analysis techniques using qualitative data are converted into quantitative data with a Likert scale. The research results showed that the development of mathematical learning modules included in good categories based on a questionnaire by a media expert with a score of 120. Average results by three material experts in excellent categories with a score of 86. The questionnaire responses of small class students obtained by 75,87 with very good categories and questionnaire responses of large class students were obtained by 74,87 with very good categories—the results based on the research that the mathematical learning module is proper to use in mathematics learning.